2014
DOI: 10.2147/cpaa.s47895
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of acetylsalicylic acid after intravenous and oral administration to healthy volunteers

Abstract: BackgroundThe pharmacology of single doses of acetylsalicylic acid (ASA) administered intravenously (250 or 500 mg) or orally (100, 300, or 500 mg) was evaluated in a randomized, placebo-controlled, crossover study.MethodsBlood and urine samples were collected before and up to 24 hours after administration of ASA in 22 healthy volunteers. Pharmacokinetic parameters and measurements of platelet aggregation were determined using validated techniques.ResultsA comparison between administration routes showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 22 publications
(18 reference statements)
6
66
1
1
Order By: Relevance
“…The results were observed in aspirin within its "antiplatelet" dosage range [22,23,25,33]. Our findings strongly suggested that aside from its anti-thrombotic properties, aspirin confers cardiovascular benefits via the attenuation of VH.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The results were observed in aspirin within its "antiplatelet" dosage range [22,23,25,33]. Our findings strongly suggested that aside from its anti-thrombotic properties, aspirin confers cardiovascular benefits via the attenuation of VH.…”
Section: Discussionsupporting
confidence: 54%
“…However, published pharmacokinetics studies on this aspirin dose have revealed contradictory C max depending on formulation, such as soluble, rapid-release, or chewable 100 mg tablets exhibiting minor differences [22,23,33]; by contrast, the enteric or controlled release tablets showed wide and significant variations [37,38]. Our in vitro results simulated human plasma levels based on 100 mg rapid-acting aspirin formulations (soluble and rapid-release tablets), whose quick action is desirable during the acute onset of symptoms, such as in MI.…”
Section: Discussionmentioning
confidence: 99%
“…These doses do not inhibition of COX-2 with COX-1 inhibition being the net pharmacological effect [8, 15]. Because of irreversible action of aspirin (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For both ASA and ticagrelor, two different final concentrations in GFP were tested: 125 and 250 μM for ASA and 250 and 500 nM for ticagrelor. The lower values were chosen to replicate typical in vivo therapeutic doses, as detected in plasma after administration of commercial tablets of ASA (500 mg) and ticagrelor (90 mg) in humans [38,39]. Higher concentration levels were chosen to replicate conditions tested in previous in vitro studies [40,41], and also to emulate higher doses of drugs in vivo .…”
Section: Methodsmentioning
confidence: 99%